Blockchain-based security support to the vehicular networks - Wu, Yufeng (Nanyang Technological University, 2020)
With the breakthrough and evolution of Vehicular Ad-hoc Network (VANET), many countries are setting up intelligent transportation system (ITS) based on it. Due to the VANET broadcast nature the communication between vehicle to vehicle (V2V) and vehicle to infrastructure (V2I), security is one of the most important issue need to be solved. In this project, preventing attacker from stealing messages during transmission is the key feature to ensure the security of the VANET. The object of this project is to design a Blockchain-based Security Support to the Vehicular Networks. I proposed a scheme by obtain the session key transmission between On Board Unit (OBU) and Trust authority (TA) with an anonymous mutual authentication, integrating with blockchain system. The Burrows–Abadi–Needham (BAN) logic is using to prove the protocol and the simulation is implement through the Automated Validation of Internet Security Protocols and Applications (AVISPA). The results have concluded that the propose can resolve the security issue of VANET.